Peningkatan Kesadaran Kesehatan Mental Sebagai Upaya Pencegahan Bullying di Sekolah Dasar - Nadhira Rasendriya Pangestu; Vidya Ajijiah; Ahmad Aitdulloh; Siti Nurazizah; Elsa Agustin; Faisa Zahro; Hanifah Arien; Tazakka Nafis (CV. Lentera Literasi Indonesia, 2026)
Bullying in elementary schools remains a serious issue that affects students’ mental health and psychological well-being. Low mental health awareness increases the risk of students becoming perpetrators or victims of bullying. This study aims to examine the effectiveness of psychoeducation in increasing mental health awareness as a preventive effort against bullying among elementary school students. This research employed a quasi-experimental method with a One Group Pretest-Posttest design involving 24 fifth-grade students at SDN Kembangarum 02 Semarang. The intervention consisted of interactive discussions, educational videos, and reflective group activities. A written quiz assessing students’ understanding of mental health and bullying prevention served as the instrument. Results show that the data met normality and homogeneity assumptions, and there was a significant increase in students’ understanding after the psychoeducation, as indicated by a Paired Sample t-Test with a significance value of 0.000 (p < 0.05). These findings confirm that psychoeducation is effective in improving mental health awareness and can serve as a preventive strategy to reduce bullying in elementary school settings. The study recommends integrating continuous mental health education into school learning activities.